2020
DOI: 10.3390/plants9081028
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification of the ABA Receptors Genes and Their Response to Abiotic Stress in Apple

Abstract: The pyrabactin resistance (PYR)/PYR1-like (PYL)/regulatory components of ABA receptor (RCAR) (known as PYLs for short) have been identified and characterized as the ABA receptors in some plants. However, little is known about the details regarding PYL family genes in the apple (Malusdomestica). In this study, we identified 13 apple PYLs, termed MdPYL1-13, which could be classified into four groups according to structural features of the amino acid sequence. The gene structures and conserved motifs analysis fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 55 publications
3
12
0
Order By: Relevance
“…Overall, except PYL4, PYL11 and PYL14 , all CsPYL genes increased more or less under ABA treatment. This was similar to the result of apple PYL genes under ABA treatment ( Hou et al, 2020 ), the expression of all MdPYLs except for MdPYL11 exhibited significant increases by ABA treatment. However, some GhPYL genes were down-regulated under ABA treatment in cotton.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Overall, except PYL4, PYL11 and PYL14 , all CsPYL genes increased more or less under ABA treatment. This was similar to the result of apple PYL genes under ABA treatment ( Hou et al, 2020 ), the expression of all MdPYLs except for MdPYL11 exhibited significant increases by ABA treatment. However, some GhPYL genes were down-regulated under ABA treatment in cotton.…”
Section: Discussionsupporting
confidence: 86%
“…According to the phylogenetic tree analysis ( Fig. 3 ), PYL genes of C. sativus , A. thaliana , O. sativa, G. max, V. vinifera, B. distachyon and M. domestica were divided into three groups, which were consistent with the grouping of rice ( Yadav et al, 2020 ), Brassica napus ( Di et al, 2018 ), cotton ( Zhang et al, 2017 ) and rubber trees ( Guo et al, 2017 ), but were different from the groupings of the apple which were divided into four groups ( Hou et al, 2020 ). This difference may be due to the diversity of different species sequences.…”
Section: Discussionmentioning
confidence: 74%
“…Besides, apple tissue culture seedlings were cultured in a specific medium, and the environmental temperature was adjusted to 4 °C and 40 °C, respectively. After the above five stress treatments, samples of apple tissue culture seedlings were collected at 0, 6, 12, and 24 h respectively, frozen rapidly with liquid nitrogen, and stored in −80 °C refrigerator for succedent experiments [ 68 ]. For all treatments, three biological replicates were collected.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, it has been reported that the AtPYL1 closely clustered with BrPYL1 and overexpression of BrPYL1 promoted the seed germination of Arabidopsis under ABA application (Li et al 2017). Hou et al (2020) identified 13 MdPYLs in Malus domestica and the results of yeast twohybrid assays verified that MdPYLs had an interaction with two 2C protein phosphatases (MdPP2C65 and MdPP2C72). However, there is little information on PYLs in Chinese cabbage and the expression modes of BrPYLs in response to different abiotic stresses still have not been reported.…”
Section: Introductionmentioning
confidence: 85%
“…It has been reported that there were 14 PYLs in the Arabidopsis thaliana genomes (Bai et al 2019). Simultaneously, the homologous genes were determined in other plant genomes, containing 14 PYLs in tomato (González-Guzmán et al 2014), 12 PYLs in rice (Tian et al 2015, Hou et al 2020, 46 PYLs in Brassica napus (Di et al 2018), 29 PYLs in tobacco (Bai et al 2019), and 14 PYLs in rubber tree (Guo et al 2017). It has been reported that when OsPYL9 was overexpressed in transgenic Arabidopsis and rice plants, the tolerance to drought stress was enhanced significantly and leaf senescence was delayed (Zhao et al 2016).…”
Section: Introductionmentioning
confidence: 97%